Dose and formulation of azithromycin in mass drug administration studies: a systematic review protocol. Issue 1 (30th May 2019) - Yue, Yan; Xiong, Tao; Zeng, Linan; Choonara, Imti; Qazi, Shamim; Chen, Hongju; Mu, Dezhi
Abstract : Introduction: Azithromycin has been given for tropical infectious diseases such as trachoma and yaws by mass drug administration (MDA). As well as controlling the infectious disease in question, MDA may have a beneficial effect in reducing mortality in young children. However, the dose, formulation, frequency and duration of azithromycin used in certain infectious diseases may vary in different studies, and these differences may have impacts on the effectiveness of azithromycin MDA. Furthermore, whether the dose, formulation, frequency and duration are associated with the effectiveness of azithromycin for reducing child mortality—if indeed this effect can be confirmed—remain unknown. In this study, we will investigate whether different strategies such as different dose, formulation, frequency and duration affect the effectiveness of azithromycin MDA on the prevalence of certain infectious diseases or child mortality. Methods and analysis: A narrative systematic review will be conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. PubMed, Embase, the Cochrane Central Register of Controlled Trials, Web of Science, ClinicalTrials.gov and WHO International Clinical Trials Registry Platform will be searched. No language restrictions will be applied. All randomised/quasi-controlled trials, observational studies (cross-sectional studies, cohort studies and case–control studies), case series and registered protocols will be considered. Dose, duration, frequency, rounds and formulations of azithromycin used in MDA will be collected and reviewed. The outcomes will be disease prevalence/control in children and child mortality. Data from the individual studies will not be pooled. Ethics and dissemination: Formal ethical approval is not required since data will be collected from published studies. This systematic review will be published in a peer-reviewed journal and presented at conference meetings. PROSPERO registration number: CRD42018114902